Impelementasi Penerapan Kurikulum Merdeka pada Mata Pelajaran Seni Budaya dan Prakarya (SBdP) Siswa Kelas IV - Kalista Musdalifa; Yun Ratna Lagandesa; Sisriawan Lapasere; Kadek Hariana; Dyah Rahmawati (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The independent curriculum was present because of the Covid-19 pandemic at the end of December 2019, becoming one of the points where the continuity of education, especially in Indonesia, experienced changes. The learning crisis that occurred accompanied by the emergency conditions of the Covid-19 pandemic had a major impact on changes in education in Indonesia. Based on the results of observations conducted by researchers at SDN Inti No. 2 Pewunu, teachers are able to apply indicators in implementing the independent curriculum. These teachers have been able to implement the independent curriculum in accordance with the guidelines contained in the independent curriculum book and are implemented comprehensively. There are several steps in the independent curriculum learning model, especially in Arts and Crafts subjects, including apperception activities, modeling, constructivism, inquiry, learning communities, assessment, asking questions and reflection. For example, activities such as asking students to create works in Arts and Crafts learning are carried out by working together in groups, which can hone students to be able to work together and think critically. This study shows that implementing the independent curriculum in elementary school, especially in Arts and Crafts, helps improve students' teamwork and critical thinking. The use of constructivist activities, inquiry models, and reflection makes students more engaged in learning. Additionally, group-based tasks and assessments improve their understanding and encourage creativity. This approach provides teachers with the opportunity to adapt their methods to better meet students' needs in the post-pandemic education era.